Cataloguing the dead: breathing new life into pseudokinase research - Shrestha, Safal (FEBS J, 2020)
Pseudoenzymes are present within many, but not all, known enzyme families and lack one or more conserved canonical amino acids that help define their catalytically active counterparts. Recent findings in the pseudokinase field confirm that evolutionary repurposing of the structurally defined bilobal protein kinase fold permits distinct biological functions to emerge, many of which rely on conformational switching, as opposed to canonical catalysis. In this analysis, we evaluate progress in evaluating several members of the ‘dark’ pseudokinome that are pertinent to help drive this expanding field. Initially, we discuss how adaptions in erythropoietin‐producing hepatocellular carcinoma (Eph) receptor tyrosine kinase domains resulted in two vertebrate pseudokinases, EphA10 and EphB6, in which co‐evolving sequences generate new motifs that are likely to be important for both nucleotide binding and catalysis‐independent signalling. Secondly, we discuss how conformationally flexible Tribbles pseudokinases, which have radiated in the complex vertebrates, control fundamental aspects of cell signalling that may be targetable with covalent small molecules. Finally, we show how species‐level adaptions in the duplicated canonical kinase protein serine kinase histone (PSKH)1 sequence have led to the appearance of the pseudokinase PSKH2, whose physiological role remains mysterious. In conclusion, we show how the patterns we discover are selectively conserved within specific pseudokinases, and that when they are modelled alongside closely related canonical kinases, many are found to be located in functionally important regions of the conserved kinase fold. Interrogation of these patterns will be useful for future evaluation of these, and other, members of the unstudied human kinome.